Perilaku Over Protective Orang Tua dengan Penyesuaian Diri Remaja di SMA Negeri 1 Wiradesa - Moh Edy Musthofa (Fakulatas Dakwah IAIN Salatiga, 2020)
Abstract The responsibility of parents fulfills the needs of children in order to develop their entire existence, these needs include biological and psychological such as feeling safe, loved, understood as children, so that children can grow and develop in harmony. Many parents deliberately or not over protective behavior. Correlational quantitative descriptive method with over protective behavior scale of parents contains statements that are favorable and unfavorable. The sample in this study was 150 students from a population of 300 grade 2 students of SMA Negeri 1 Wiradesa. The results showed that there was a moderate relationship between the over protective behavior of parents and adolescents' self-adjustment which was indicated by the value (r) of -0.433 ranging from 0.40 to 0.599. This means that the over protective behavior of parents has a moderate impact on adolescent adjustment. In addition, there is an effective contribution of over protective behavior of parents with adolescent adjustment of grade 2 SMA 1 Wiradesa by 18.8% while the remaining 81.2% comes from other factors. AbstrakTanggung jawab orang tua mencukupi kebutuhan anak guna mengembangkan keseluruhan eksistensinya, kebutuhan tersebut meliputi biologis maupun psikologis seperti rasa aman, dikasihi, dimengerti sebagai anak, sehingga anak dapat tumbuh dan berkembang kearah harmonis. Banyak orang tua yang dengan sengaja maupun tidak berperilaku over protective. Metode deskriptif kuantitatif korelasional dengan skala perilaku over protective orang tua memuat pernyataan yang bersifat favourable dan unfavourable. Sampel dalam penelitian ini 150 siswa dari populasi 300 siswa kelas 2 SMA Negeri 1 Wiradesa. Hasil penelitian terdapat hubungan yang sedang antara perilaku over protective orang tua dengan penyesuaian diri pada remaja yang ditunjukkan dengan nilai (r) sebesar -0.433 berkisar 0.40-0.599. Artinya perilaku over protective orang tua berdampak sedang terhadap penyesuaian diri remaja. Selain itu terdapat sumbangan efektif perilaku over protective orang tua dengan penyesuaian diri remaja siswa kelas 2 SMA 1 Wiradesa sebesar 18.8% sedangkan sisanya sebesar 81.2% berasal dari faktor lain.